2017
DOI: 10.1016/j.kint.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Patients double-seropositive for ANCA and anti-GBM antibodies have varied renal survival, frequency of relapse, and outcomes compared to single-seropositive patients

Abstract: Co-presentation with both ANCA and anti-GBM antibodies is thought to be relatively rare. Current studies of such ‘double-positive’ cases report small numbers and variable outcomes. To study this further we retrospectively analyzed clinical features and long-term outcomes of a large cohort of 568 contemporary patients with ANCA-associated vasculitis, 41 patients with anti-GBM disease, and 37 double-positive patients with ANCA and anti-GBM disease from four European centers. Double-positive patients shared chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
201
3
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(231 citation statements)
references
References 36 publications
13
201
3
14
Order By: Relevance
“…The authors hypothesize that MPO-ANCA recognizing linear and conformational epitopes may arise sequentially, via a process of inter-and intramolecular epitope spreading (87). We recently analyzed the outcomes of a large cohort of these "doublepositive" patients from four centers in Europe, and found that they experience the early morbidity and mortality of anti-GBM disease, with severe kidney and lung disease at presentation, requiring aggressive immunosuppressive therapy and plasma exchange (88). During long-term follow-up, they relapsed at a frequency comparable to a parallel cohort of patients with AAV, suggesting they warrant more careful long-term follow-up and maintenance immunosuppression, unlike patients with single-positive anti-GBM disease.…”
Section: Post-transplant Anti-gbm Disease In Alport Syndromementioning
confidence: 99%
“…The authors hypothesize that MPO-ANCA recognizing linear and conformational epitopes may arise sequentially, via a process of inter-and intramolecular epitope spreading (87). We recently analyzed the outcomes of a large cohort of these "doublepositive" patients from four centers in Europe, and found that they experience the early morbidity and mortality of anti-GBM disease, with severe kidney and lung disease at presentation, requiring aggressive immunosuppressive therapy and plasma exchange (88). During long-term follow-up, they relapsed at a frequency comparable to a parallel cohort of patients with AAV, suggesting they warrant more careful long-term follow-up and maintenance immunosuppression, unlike patients with single-positive anti-GBM disease.…”
Section: Post-transplant Anti-gbm Disease In Alport Syndromementioning
confidence: 99%
“…ELISA invariably shows the presence of anti-GBM antibodies in serum of these patients. One-third of the patients can have circulating ANCA, mainly MPO-ANCA, in addition to anti-GBM antibody [43]. ANCA can precede the development of anti-GBM antibody by months or years.…”
Section: Histopathologymentioning
confidence: 99%
“…ANCA can precede the development of anti-GBM antibody by months or years. The patients can be doubly positive for anti-GBM and C-ANCA or P-ANCA [43]. Double-positive patients have characteristics similar to those of ANCA-associated vasculitis including older age and longer symptom duration before diagnosis and features of anti-GBM disease such as kidney and lung involvement at presentation [43].…”
Section: Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In einer der bis dato größten Kohortenstudien zur Anti-GBM-Erkrankung war bei Patienten mit einer additiven Plasmapheresebehandlung kein relevanter Langzeitbenefit im Vergleich zur Standardimmunsuppression mit CYC und GC erkennbar, es bestand allerdings ein erheblicher Selection-Bias zum Einsatz der Plasmapherese [15]. Andere Kohortenstudien konnten zeigen, dass eine bereits bestehen- Bis zu 50 % Patienten mit Anti-GBM-Erkrankung sind auch MPO-oder PR3-ANCA-positiv [44]. Die Daten zur Prognose von ANCA-positiven Patienten mit Anti-GBM-Erkrankung sind uneinheitlich -es wurden sowohl eine höhere als auch niedrige Wahrscheinlichkeit eines Erhalts der Nierenfunktion bei positivem ANCA berichtet [3,15,44].…”
Section: » Entscheidend Für Dieunclassified